2020
DOI: 10.21776/ub.profit.2020.014.02.11
|View full text |Cite
|
Sign up to set email alerts
|

Peran Mediasi Financial Behaviour Pada Financial Literacy Terhadap Firm Performance

Abstract: Financial literacy is a very important thing to be discussed further. In running a company or businesses in small, medium and large sectors, knowledge is needed to be able to run the business or company operations. This paper summarizes empirical research articles published between 2009 and 2019 that raise the topic of financial literacy. The articles reviewed in this paper look at the research gap, strengthen support for existing theories, and identify patterns among previous research. This review is expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…They refer to the ability to understand and use the company's financial statements to calculate fundamental financial ratios that allow the business to be adequately evaluated and managed. In this way, the entrepreneur's financial literacy is an important determinant of a company's performance, and various research around the world has demonstrated the relationship between these variables (Wati et al 2021;Augustin et al 2020;Agyapong and Attram 2019;Engström and McKelvie 2017).…”
Section: Financial Literacy and Company Performancementioning
confidence: 99%
“…They refer to the ability to understand and use the company's financial statements to calculate fundamental financial ratios that allow the business to be adequately evaluated and managed. In this way, the entrepreneur's financial literacy is an important determinant of a company's performance, and various research around the world has demonstrated the relationship between these variables (Wati et al 2021;Augustin et al 2020;Agyapong and Attram 2019;Engström and McKelvie 2017).…”
Section: Financial Literacy and Company Performancementioning
confidence: 99%
“…Financial behavior can be explained as the application of psychological principles in the field of finance to understand and analyze decision-making, whether in household contexts, financial markets, or organizations (Hidayati et al 2016). Augustin et al (2020) suggest that individuals with good financial behavior tend to make more directed decisions in managing their businesses. Moreover, Atkinson and Messy (2012) propose that an individual's financial behavior significantly and positively impacts their financial performance and the selection of financial services and products.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Huston identified the financial knowledge component after reviewing 71 studies, namely; basic concepts of money, purchasing power, personal financial accounting concepts, and transfer of resources between periods, which include loans, savings, and investments, protection (Huston, 2010a). In this study, s were adopted from Huston, Garg & Singh, OECD / INFE, OJK, and Augustin [17], [24], [32], [33], [34] . Digital financial knowledge is financial knowledge seen from the media used, that is digital media.…”
Section: Fig 2 Kerangka Konseptual A) Financial Knowledgementioning
confidence: 99%